Thermodynamic assessment on the integration of thermo-electric modules in a wood fireplace - Baldini, Andrea; Cerofolini, Luca; Fiaschi, Daniele; Manfrida, Giampaolo; Talluri, Lorenzo (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The growing demand for electricity produced from renewable sources and the development of new technologies for the combustion of biomass, arose a growing interest on the possible coupling of thermoelectric modules with stove-fireplaces. The current thermoelectric generators have a solid structure, do not produce noise, do not require maintenance and can be used for the recovery of waste heat or excess, at the same time they hold a very low conversion efficiency and they need an adequate cooling system.
Keywords: stove-fireplaces; thermoelectric module; thermodynamic assessment; combustion of biomass; renewable sources; piec kominkowy; moduł termoelektryczny; ocena termodynamiczna; spalanie biomasy; źródła odnawialne